Pengaruh Penggunaan Lms Webcode Berbasis Moodle Terintegrasi Pbl Terhadap Hasil Belajar Murid Pada Elemen Pemrograman Web - Faniah Iftitakhul Kamilah; Martini Dwi Endah Susanti (CV. SINAR HOWUHOWU, 2026)
Student learning outcomes in the Web Programming unit at the vocational high school (SMK) level remain a challenge during the implementation of the kurikulum Merdeka (Independent Curriculum), particularly regarding the mastery of cognitive concepts and practical psychomotor skills. This study aimed to analyze the impact of using the Moodle-based